Efficacy of post-emergence herbicide imazethapyr for weed management in different mungbean (Vigna radiata) cultivars - GURIQBAL SINGH; NAVNEET AGGARWAL; HARI RAM (The Indian Journal of Agricultural Sciences, 2014)
Three mungbean cultivars, viz. ML 267, ML 818 and PAU 911 showed good degree of tolerance to imazethapyr sprayed at different doses and at different times during 2008 and 2009. Application of imazethapyr at 75 and 100 g/ha at 15 days after sowing (DAS) and imazethapyr 100 g/ ha 25 DAS gave good control of weeds and the weed control efficiency was comparable to that of two hand weedings. Use of imazethapyr at 100 g/ha at 15 DAS gave the highest grain yield of mungbean. Application of imazethapyr at 75 and 100 g/ha at 15 DAS resulted in 144.6 and 146.4% higher grain yield respectively over unweeded control during first year of study, while the corresponding values in second year of study were 79.2 and 85.6%. Application of imazethapyr at 100 g/ha at 15 DAS gave the highest gross and net returns followed by imazethapyr at 75 g/ha sprayed at 15 DAS.